184k views
3 votes
Given f(x) = x², g(x) = 2x - 1, and h(x) = x - 4;
Find h(f(x)).

2 Answers

2 votes

Answer:
h(f(x))=\Large\boxed{x^2-4}

Explanation:

Given information


f(x)=x^2


g(x)=2x-1


h(x)=x-4

Requirement of the question


\text{Find the expression for}~h(f(x))

Substitute the f(x) expression into h(x)


h(f(x))=(x^2)-4

Simplify the expression


h(f(x))=\Large\boxed{x^2-4}

Hope this helps!! :)

Please let me know if you have any questions

User Iruleonu
by
5.2k points
3 votes

Answer: x²-4

Explanation:

User BaptisteB
by
5.3k points